Analysis Of Bank Health Level With RGEC Method (Risk Profile, Good Corporate Governance, Earnings, And Capital) On PT. Bank Bengkulu - Saputra, Rangga; Soleh, Ahmad; Febliansa, M. Rahman (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This research aims to determine the health level of PT. Bank Bengkulu in the periode of 2020-2022 using the RGEC method (Risk Profile, Good Corporate Governance, Earning, and Capital). Based on the results of assessing the bank’s health level by applying the RGEC method at PT. Bank Bengkulu is assessed based on factors,namely 1. Risk Profile, the result of the NPL ratio in 2020 amounted to 0,78%, in 2021 amounted to 0,91%, and ini 2022 amounted to 1,05%, which is said to be very healthy. The LDR ratio result in 2020 amounted to 91,78%, in 2021 amounted to 93,41%, and in 2022 amounted to 90,45%, which can be said to be quite healthy. 2. The bank’s Good Corporate Governance carried out a self-assessment with GCG in 2020 PK1, 2021 PK 3, and 2022 PK 1. 3. Earnings, the ROA ratio in 2020 amounted to 2,05%, in 2021 amounted to 1,43%, and in 2022 amounted to 1,89%, This is said to be healthy. The BOPO ratio result in 2020 amounted to 73,86%, and in 2021 amounted to 80,01%, and in 2022 amounted to 75,13%, which can be said to be very healthy. 4. Capital, the result of the CAR ratio in 2020 amounted to 24,24%, in 2021 amounted to 22,92%, and in 2022 amounted to 24,52%, which can be said to be very healthy. Results from research on the health level of PT. Bank Bengkulu received PK 1 in 2020 and 2022, namely with a very healthy statement and PK 2 in 2021, namely with a healthy statemeny.